Empowerment of the Situnggaling Community in Improving the Economy through Entrepreneurship Training in Shallot Processing - Rangkuti, Dhita Adriani; Siregar, Rosmita Sari; Mesrawati, Mesrawati; Wulandari, Bayu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Situnggaling village is a fertile area, where the area has the potential to produce superior agricultural crops such as shallots. The program is implemented to provide education and training as a means of understanding the community about the natural potential of the village and this program will also provide education and training in the field of entrepreneurship which is expected to grow the community's economy and income.Activity This community service is carried out by an implementing team from an economics lecturer at Prima Indonesia University where this program is the KEDAIREKA Matching Fund program promoted by the Ministry of Education, Culture, Research, and Technology and in collaboration with partners namely BACRIS where this program is entitled Empowering the Situnggaling Community in Improvement of the Economy through Entrepreneurship Training on Shallot Processing and was welcomed positively by the local government and the people who were involved as training participants.